Estudio comparativo de la adherencia al tratamiento en pacientes con diagnóstico de hipertensión arterial que acuden al servicio de medicina interna en consulta externa del Hospital Manuel Ygnacio Monteros IESS vs. Hospital Regional Isidro Ayora de la ciudad de Loja - Flores Martínez, Yessenia Pilar (2014)
Objectives: Assess the adhesion, investigating the psychological and socio-economic factors and time knowing the diagnosis and treatment of hypertension in patients attending the service of internal medicine at external consultation of the Hospital Manuel Ygnacio Monteros IESS vs. Hospital Regional Isidro Ayora in the city of Loja. Patients and methods: It was a quantitative, descriptive, cross-sectional study.The total population was 150 patients, divided equally in each hospital. The Test of Morisky Green Levine and an autoelaborada on the psychological and socioeconomic factors survey was used for data collection that influence in adherence to treatment. Results: 36% shows of established and 37.3% of patients of the Hospital Manuel Ygnacio Monteros and Hospital Regional Isidro Ayora respectively, are adherent to treatment. In reference to the socio-economic factors in the Hospital Manuel Ygnacio Monteros was observed predominance of: female gender, which corresponds to the 81.5%, with an age between age 61 and older Strip (48.1%); 37% has superior instruction; 66.7% married; 55.6% are employed and 63% take medication in the hospital; the59.3% was diagnosed and receive treatment for their high blood pressure more than 6 years ago. The 51.9% do not have the control of tension figures. In the Hospital Regional Isidro Ayora the situation is similar the 53.6% are age 61 and older women (32.1%); 60.7% have primary education; 57.1% are married; 28.6% have employment; 85.7% acquire the medication at the hospital, but also themselves; buy it the 85.7% was diagnosed of hypertension over 6 years ago, and 75% are treated equally 6 years. The 53.6% do not have the control of tension figures. Key words: Hypertension, therapeutic adherence and treatment compliance